Antimicrobial and antioxidant efficiency of nanoemulsion-based edible coating containing ginger (Zingiber officinale) essential oil and its effect on safety and quality attributes of chicken breast fillets. (February 2018) - Noori, Soheila; Zeynali, Fariba; Almasi, Hadi
Abstract: Nanoemulsion-based edible sodium caseinate coating containing ginger essential oil (GEO) (3 and 6% wt) was applied onto chicken breast fillet to extend its shelf life. GC-MS analysis showed that the most components of GEO were α-zingiberene (24.96%) and then β-sesquiphellandrene (12.74%). Comparison between conventional emulsion and nanoemulsion-based coatings was applied by particle size, polydispersity index and ζ-potential analyses. Antibacterial potential of active coatings was more than their antioxidant activity and it was significantly (p < 0.05) increased when nanoemulsion was fabricated. Nanoemulsion based edible coatings with 6% of GEO nanoemulsion caused to significant decrease of total aerobic psychrophilic bacteria of refrigerated chicken fillets during 12 days. The effect of GEO on TBARS levels of fillets was not significant. The lowest color difference and cooking loss were obtained for nanoemulsion coated samples. The highest total acceptance was recorded for coated fillets with 6% of GEO nanoemulsion during storage. Generally the GEO nanoemulsion was more effective than its conventional emulsion in extending the durability of chicken breast fillets. Highlights: Nanoemulsion resulted as an effective carrier for ginger essential oil (GEO). Edible coatings with GEO loaded emulsions and nanoemulsions were prepared. Antimicrobial activity was increased by increasing GEO especially in nanoemulsions. Nanoemulsion loaded coating had more effect on quality attributes of chicken breast. Overall acceptability of fillets coated with GEO nanoemulsion was more than emulsion.